The Role of Public Libraries in Meeting the Information Needs of the Illiterate Rural Dwellers in Fostering National Development in Nigeria - Onohwakpor , J.E. (MiddleBelt Journal of Library and Information Science, 2014)
This paper focuses on the role of public library in meeting the information needs of illiterate adult rural dwellers in fostering national development. Information is a vital tool for national development. It helps the individual to become capable and productive in their social, economy and political obligations that are recipes of nation’s development. The concept of illiterate rural adults is explained as citizens whose settlement area is less than the population of five thousand and lacks the basic amenities and social infrastructures. The concept of national development was explained in areas of human endeavour that leads to every citizen contributing his\her knowledge to nation’s development. If the ordinary man in the society had to contribute to nation’s development, he must be abreast of the information that will broaden his knowledge of areas of operation. The chief source of this information distributor is the public library. The role of public library to illiterate adult rural dwellers was spelt out. The paper also pointed out the possible challenges of public libraries in meeting the information needs of illiterate rural adults and possible solutions to these challenges for effective public library services.